Survival After Liver Transplantation: An International Comparison Between the United States and the United Kingdom in the Years 2008–2016. Issue 7 (9th November 2021) - Ivanics, Tommy; Wallace, David; Abreu, Phillipe; Claasen, Marco P.A.W.; Callaghan, Chris; Cowling, Thomas; Walker, Kate; Heaton, Nigel; Mehta, Neil; Sapisochin, Gonzalo; van der Meulen, Jan
Abstract : Background: Compared with the United States, risk-adjusted mortality in the United Kingdom has historically been worse in the first 90 d following liver transplantation (LT) and better thereafter. In the last decade, there has been considerable change in the practice of LT internationally, but no contemporary large-scale international comparison of posttransplant outcomes has been conducted. This study aimed to determine disease-specific short- and long-term mortality of LT recipients in the United States and the United Kingdom. Methods: This retrospective international multicenter cohort study analyzed adult (≥18 y) first-time LT recipients between January 2, 2008, and December 31, 2016, using the Organ Procurement and Transplantation Network/United Network for Organ Sharing and the UK Transplant Registry databases. Time-dependent Cox regression estimated hazard ratios (HRs) comparing disease-specific risk-adjusted mortality in the first 90 d post-LT, between 90 d and 1 y, and between 1 and 5 y. Results: Forty-two thousand eight hundred seventy-four US and 4950 UK LT recipients were included. The main LT indications in the United States and the United Kingdom were hepatocellular carcinoma (25.4% and 24.9%, respectively) and alcohol-related liver disease (20.3% and 27.1%, respectively). There were no differences in mortality during the first 90 d post-LT (reference: United States; HR, 0.96; 95% confidence interval [CI], 0.82–1.12). However, between 90 d and 1 y (HR, 0.71; 95% CI, 0.59–0.85) and 1 and 5 y (HR, 0.71; 95% CI, 0.63–0.81]) the United Kingdom had lower mortality. The mortality differences between 1 and 5 y were most marked in hepatocellular carcinoma (HR, 0.71; 95% CI, 0.58–0.88) and alcohol-related liver disease patients (HR, 0.64; 95% CI, 0.45–0.89). Conclusions: Risk-adjusted mortality in the United States and the United Kingdom was similar in the first 90 d post-LT but better in the United Kingdom thereafter. International comparisons of LT may highlight differences in healthcare delivery and help benchmarking by identifying modifiable factors that can facilitate improved global outcomes in LT.